Navigating Into the Future or Driven by the Past. (March 2013) - Seligman, Martin E. P.; Railton, Peter; Baumeister, Roy F.; Sripada, Chandra
Prospection (Gilbert & Wilson, 2007), the representation of possible futures, is a ubiquitous feature of the human mind. Much psychological theory and practice, in contrast, has understood human action as determined by the past and viewed any such teleology (selection of action in light of goals) as a violation of natural law because the future cannot act on the present. Prospection involves no backward causation; rather, it is guidance not by the future itself but by present, evaluative representations of possible future states. These representations can be understood minimally as "If X, then Y " conditionals, and the process of prospection can be understood as the generation and evaluation of these conditionals. We review the history of the attempt to cast teleology out of science, culminating in the failures of behaviorism and psychoanalysis to account adequately for action without teleology. A wide range of evidence suggests that prospection is a central organizing feature of perception, cognition, affect, memory, motivation, and action. The authors speculate that prospection casts new light on why subjectivity is part of consciousness, what is "free" and "willing" in "free will, " and on mental disorders and their treatment. Viewing behavior as driven by the past was a powerful framework that helped create scientific psychology, but accumulating evidence in a wide range of areas of research suggests a shift in framework, in which navigation into the future is seen as a core organizing principle of animal and human behavior.